Supply Chain Performance Measurement for One Maintenance Cycle of Broiler Plasma Farm - Elly Ismiyah (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2023)
To become a partner of a core company on a broiler plasma farm, a farmer must have good performance. The performance measurement of plasma farms was carried out by the core company with a number called performance index (IP), where this IP reflects the value of the plasma farmers that will be used by the core company to determine the next cooperative relationship. The IP calculation is done at the end of a maintenance cycle by the field extension officer (FEO) based on the results of daily reports. In determining the IP calculation, the factors seen are The Feed Consumption Rate (FCR), Mortality, and the use of drugs, vitamins, and chemicals. For Plasma farmers, the obtained IP was only a report from the results of work in one maintenance cycle, while management in the core supply chain process was not known, how the farm's performance was. Prior research succeeded in designing an instrument for Assess Supply Chain Performance for Broiler Plasma Farms using five core processes SCOR and Analytical Hierarchy (AHP) for weighting. This research will measure the supply chain performance of several Plasma farms with the designed instrument. From the results of this performance measurement, plasma farmers will get an idea of which core processes need to be improved so that the performance in the next cycle will be better. In addition, this research will also look for the correlation between the performance obtained and the IP that has been assessed by the core company.